On the effect of the fiber orientation on the flexural stiffness of injection molded short fiber reinforced polycarbonate plates - Neves, N. M. (1998)
The through-thickness fiber orientation distribution of injection molded polycarbonate plates was experimentally determined by light reflection microscopy and manual digitization of polished cross sections. Fiber length distribution was determined by pyrolysis tests followed by image analysis. A statistical analysis was done to determine the confidence limits of the fiber orientation results. The fiber orientation distribution was described by using second-order orientation tensors. The throughthickness stiffness variations were determined by the orientation averaging approach. This layer stiffness distribution was used to simulate the behavior of beams subjected to three point bending with a FEM Ansys model. The results were compared with experimentally determined flexural stiffness both in the flow direction and in the transverse flow direction. The effect of flow rate and melt-temperature on stiffness and fiber orientation is discussed.